2011
DOI: 10.2478/v10207-011-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Wheat Grains with Species of Genera Fusarium in Different Localities of Slovakia in 2006-2008

Abstract: The frequency and relative density of occurrence of Fusarium spp. was evaluated on 112 wheat grain samples from different agro-ecological localities in Slovakia. The samples were collected in 2006, 2007 and 2008 from the same farmers and from the same localities every year immediately after harvest. In 2006, contamination was 95.2%, in 2007 it was 64.3%, and 71.4% in 2008. The highest average frequency of occurrence was found in Fusarium graminearum in 2006 -65%. The prevalence of Fusarium poae was ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The average contamination of samples in 2010 is the highest detected during our monitoring of the DON content in wheat samples when compared to existing published results [3]. In the samples of wheat grown between 2004 and 2008 collected from nine sites in Slovakia, the analysis found that the highest average contamination was 0.82 mg·kg −1 , in 2006 [3]. A different DON content was detected in wheat samples collected immediately after harvest, from producers in Serbia in 2004, and had an average contamination of 1.23 mg·kg −1 .…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The average contamination of samples in 2010 is the highest detected during our monitoring of the DON content in wheat samples when compared to existing published results [3]. In the samples of wheat grown between 2004 and 2008 collected from nine sites in Slovakia, the analysis found that the highest average contamination was 0.82 mg·kg −1 , in 2006 [3]. A different DON content was detected in wheat samples collected immediately after harvest, from producers in Serbia in 2004, and had an average contamination of 1.23 mg·kg −1 .…”
Section: Resultsmentioning
confidence: 57%
“…From 2010 to 2011, a 67.7% difference was observed in DON content, with the results showing a high level of sample contamination in 2010. The average contamination of samples in 2010 is the highest detected during our monitoring of the DON content in wheat samples when compared to existing published results [3]. In the samples of wheat grown between 2004 and 2008 collected from nine sites in Slovakia, the analysis found that the highest average contamination was 0.82 mg·kg −1 , in 2006 [3].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation